Elucidation of the technological conditions for the formation of alkali silicates heat-insulating products based on ash-removal of thermal power plants and liquid glass - Dryuchko Оleksandr; Bunyakina , Natalia; Shefer Оleksandr; Zakharchenko, Ruslan; Kyslytsia, Dmytro; Moskalenko, Marina (Academic journal Industrial Machine Building Civil Engineering, 2024)
The carried out complex study gives a reliable idea of the trends in the joint behavior of structural components in water-salt systems of nitrate precursors of neodymium, cesium, strontium in the preparatory stages of technological regulations for both concentration and immobilization of liquid radioactive waste of the nuclear energy industrial complex 137Cs, 90Sr and thermal activation. The stages of such transformations have been revealed; the patterns of complex and phase formation in systems and the factors influencing them have been clarified. It has been studied a number of physicochemical properties of the resulting intermediate phases (coordination neodymium nitrates: their composition, types of compounds, atomic crystal structure, shapes of Ln coordination polyhedra, types of ligand coordination, features and patterns of behavior in heat treatment processes. It has been established that, under the conditions of the existence of solutions, the system CsNO3 – Nd(NO3)3 – H2O is characterized by the formation of 2 anionic complex compounds Ln3+, the system Sr(NO3)2 – Nd(NO3)3 – H2O – is of the eutonic type. The ongoing competing reactions are a powerful technological factor that has a significant impact on changes in the activity of structural forms of Ln3+. Systematized information enables to elucidate the mechanisms and kinetics of transformations of structural components in similar objects. Also, it enables to transfer the resulting system of knowledge to the promising technological solutions for the solidification of liquid radioactive wastes